2006
DOI: 10.1086/498182
|View full text |Cite
|
Sign up to set email alerts
|

Both Incubation Temperature and Posthatching Temperature Affect Swimming Performance and Morphology of Wood Frog Tadpoles (Rana sylvatica)

Abstract: In many oviparous vertebrates, hatchling phenotypes are influenced by egg incubation temperature. Many of those phenotypic traits can also acclimate to long-term thermal conditions of juveniles and adults, yet the interactive effects of prehatching and posthatching temperatures on phenotypes have not been studied. To address such interaction, we incubated eggs of wood frogs (Rana sylvatica) at two temperatures and subsequently reared larvae at three temperatures in a fully factorial design. We measured body si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 53 publications
3
41
0
2
Order By: Relevance
“…Similar to our results, Watkins and Vraspir (2006) found embryonic and larval developmental temperatures significantly affected larval wood frog (Lithobates sylvaticus) morphology. These effects resulted in altered swimming performance, which has important survival implications (Watkins and Vraspir, 2006). Considering that smaller, less developed larvae are more susceptible to pollution (Beebee, 1986;Cooke, 1979;Hopkins et al, 2014) and predators (Anderson et al, 2001;Boone et al, 2002;Gall et al, 2011;Touchon et al, 2013;Warkentin, 1995), the carry-over effects of embryonic temperature in salamanders and newts could have survival consequences in later life stages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our results, Watkins and Vraspir (2006) found embryonic and larval developmental temperatures significantly affected larval wood frog (Lithobates sylvaticus) morphology. These effects resulted in altered swimming performance, which has important survival implications (Watkins and Vraspir, 2006). Considering that smaller, less developed larvae are more susceptible to pollution (Beebee, 1986;Cooke, 1979;Hopkins et al, 2014) and predators (Anderson et al, 2001;Boone et al, 2002;Gall et al, 2011;Touchon et al, 2013;Warkentin, 1995), the carry-over effects of embryonic temperature in salamanders and newts could have survival consequences in later life stages.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, predator avoidance and insecticide sensitivity during the larval stage has been shown to be affected by embryonic rearing temperature in an Australian frog (Limnodynastes peronii) (Broomhall, 2004). Similar to our results, Watkins and Vraspir (2006) found embryonic and larval developmental temperatures significantly affected larval wood frog (Lithobates sylvaticus) morphology. These effects resulted in altered swimming performance, which has important survival implications (Watkins and Vraspir, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Such growthinduced differences in muscle structure have been shown in herring (Clupea harengus) to translate into differences in swimming performance that persist even when fish are subsequently growing at the same rate (Johnston et al, 2001). Effects of embryonic conditions on muscle development and subsequent motor performance are not restricted to fish: effects of early growth rate on tail muscle fibre numbers and swimming performance have been found in tadpoles of both toads (Arendt and Hoang, 2005) and frogs (Watkins and Vraspir, 2006), and it has been suggested that such a trade-off between early growth rate and locomotor performance is common to all vertebrates (Arendt, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In a wide range of organisms, the conditions under which an embryo develops alter the organism's phenotype in later life (Deeming 2004;Watkins and Vraspir 2006). Given the sensitivity of developmental trajectories to local conditions, one of the most intriguing questions involves conservatism in phenotypic traits in wide-ranging species.…”
Section: Introductionmentioning
confidence: 99%